Synderesis vs. Consequentialism and Utilitarianism in Workplace Bullying Prevention - Jolita Vveinhardt; Mykolas Deikus (Social Inclusion, 2025)
The existence of workplace bullying in modern organizations is, first of all, a serious moral challenge. Since bullying characterized by intense and long‐lasting persecution of the target causes serious negative consequences for organizations, there are proposals to base the prevention of this phenomenon on utilitarianism. However, some studies show that the ethics that judges the goodness of an action by consequences causes many problems at the level of interpersonal relationships. Therefore, in the context of workplace bullying, it is proposed to consider the scholastic idea of synderesis. The article theoretically examines three alternatives to bystanders’ decisions based on the ideas of consequentialism, utilitarianism, and synderesis: to act constructively actively (to support the victim), to act destructively actively (to support the persecutor), and to act destructively passively (not to intervene in the conflict). Considering that different schools of consequentialism and utilitarianism cannot guarantee constructive behaviour of bystanders, the decisions inspired by the conscience guided by synderesis can be a suitable alternative that can be easily implemented in practice.